Isolation and Identification of Actinomycetes Associated with Moss on the Surface of the Borobudur Temple Stone - Ade Lia Putri; Debora Christin Purbani; Atit Kanti; Mia Kusmiati; Moh Habibi (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Mosses growing on the surface of the Borobudur Temple will affect the aesthetic value of the temple. Interaction between moss and actinomycetes may trigger the growth of moss that can cause an increase in biodeterioration of stone. The purpose of this study was to isolate and identify the actinomycetes associated with moss on the surface of decayed stone of Borobudur Temple as well to assess their ability for phosphate solubilizing. Actinomycetes were isolated using serial dilution method and were identified based on 16S rRNA gene sequences. A total of 37 actinomycetes were isolated from three sampling sites. The isolates found belong to five genera (Gordonia, Microbacterium, Micromonospora, Nocardia, and Streptomyces) and distributed among four families (Microbacteriaceae, Micromonosporaceae, Nocardiaceae, and Streptomycetaceae). Isolates of actinomycetes composed of 19 Streptomyces Group and 18 Rare Actinomycetes Group. Nineteen isolates (51.35%) were identified as genus Streptomyces. Seventeen isolates (45.94%) showed abilities to release soluble phosphate and most of the isolates belong to the genus Streptomyces. The isolates have been collected will be deposited to Indonesian Culture Collection (InaCC) to enrich the collection of actinomycetes from ancient stone in Indonesia and will be used as a source of reference material research, taxonomic, or as source for further study.